Fecal Calprotectin Is Not Affected by Pregnancy: Clinical Implications for the Management of Pregnant Patients with Inflammatory Bowel Disease. Issue 7 (July 2017) - Julsgaard, Mette; Hvas, Christian L.; Gearry, Richard B.; Vestergaard, Thea; Fallingborg, Jan; Svenningsen, Lise; Kjeldsen, Jens; Sparrow, Miles P.; Wildt, Signe; Kelsen, Jens; Bell, Sally J.
Abstract : Background: Noninvasive biomarkers of inflammation for monitoring inflammatory bowel disease (IBD) are important in pregnancy. Clinical and laboratory markers are often affected by the physiological adaption that occurs during pregnancy, although, few, if any, data exist on fecal calprotectin (FC). We investigated FC concentrations in pregnant controls and IBD women, and whether FC correlated with physician global assessment (PGA), C-reactive protein (CRP), and Harvey–Bradshaw Index (HBI)/Simple Clinical Colitis Activity Index (SCCAI) before and after pregnancy, as well as during each trimester. Methods: The study is a prospective multicenter study of 46 pregnant women with and 21 without IBD in Denmark, Australia, and New Zealand. Demographics, clinical parameters, and HBI/SCCAI were recorded. Stool and blood samples were obtained to determine FC and CRP concentrations. Results: From pregnant IBD women and pregnant controls, 174 and 21 fecal samples were collected, respectively. The median FC concentration in pregnant IBD women was 131 μg/g (range 0–3600) and in controls 0 μg/g (range 0–84) ( P < 0.0001). FC strongly correlated with PGA at all 5 timepoints (r ≥ 0.80; P < 0.0001) and with HBI/SCCAI before (r = 0.66; P < 0.0001) and after pregnancy (r = 0.47; P < 0.003) but not during pregnancy ( P > 0.05). An FC cutoff concentration of 250 μg/g significantly correlated with active disease according to PGA in all 5 periods ( P ⩽ 0.0002). CRP only significantly correlated with FC ( P = 0.0007) and PGA in the second trimester ( P = 0.0003). No significant correlation was found between CRP and HBI/SCCAI at any timepoint ( P > 0.05). Conclusions: The physiological changes that occur during pregnancy do not affect FC, in contrast to CRP and HBI/SCCAI. The combined use of FC and PGA seems optimal to assess disease activity in IBD during pregnancy. Abstract : Article first published online 11 May 2017.